Microbial control of white grubs with entomopathogenic fungi and its value in integrated pest management (IPM) in Nepal - G. C., Yubak Dhoj; Keller, Siegried; Nagel, Peter (Tribhuvan University Journal, 2006)
With an objective to explore the possibility of biocontrol of white grubs using entomopathogenic fungi, an exploratory tudy was conducted in the Syangja and Parbat districts in nepal in the winter of 2001/2002. In order to explore the occurrence of indigenous fungal pathogens of white grubs, field and laboratory experiments were carried out and information were collected from all available sources. Upon collection of the white grubs the entomopathogenic fungus Metarhizium anisopliae was found to be associated with white grubs in fields with arable crop. Disease prevalence was between ) and 2% depending on host origin and species. Bioassays revealed that the Nepalese isolates of this fungus species were as pathogenic as a Swiss isolate used for comparison purposes. Therefore, Future work will be done exclusively with Nepalese isolates. Analysis of soils from three different regions showed that M. anisopliae is common and was present in about 50% of the samples irrespective of their origin. However, the fungus densities were low. Another entomopathogenic fungus, Beauveria bassiana, was isolated as well from a few soil samples. Based on these first results, the possibilities to develop mycoinsecticides and to integrate them into existing pest management (IMP) systems are considered as very promising. In the meantime a project funded by Helvetas has been initiated at Tribhuvan University (TU), Institute of Agriculture and Animal Sciences (IAAS), Rampur, Chitwan, Nepal. Key words: Biological control, entomopathogenic fungi, Metarhizium anisopliae, Scarabaeidae, white grubs, Nepal.